2001
DOI: 10.1086/320527
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Blood Culture for Hospitalized Patients Who Are Receiving Antibiotic Therapy

Abstract: We conducted a retrospective study to determine the yield of blood samples drawn for culture during the initial 72 h of antibiotic therapy given to 139 patients who were admitted to the hospital for community-acquired infections or fever. The yield of these blood cultures was predictable and rarely (in only 1 patient [0.72%]) isolated new pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 8 publications
6
57
0
10
Order By: Relevance
“…Antibiotic treatment before sampling reduces the effectiveness of blood cultures. 6,7 The advantage of a DNA-based detection system is that the microorganism causing sepsis does not have to be live at the time of sampling. In our research, detection of pathogens by SeptiFast was not affected by start of antibiotic treatment before sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic treatment before sampling reduces the effectiveness of blood cultures. 6,7 The advantage of a DNA-based detection system is that the microorganism causing sepsis does not have to be live at the time of sampling. In our research, detection of pathogens by SeptiFast was not affected by start of antibiotic treatment before sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sensitivity of blood culture is greatly reduced when samples are obtained after antimicrobial therapy has started. 6,7 Molecular methods allow rapid detection of the microorganisms involved in severe infections, leading to more efficient and more accurately targeted early therapeutic interventions, which could mean major clinical benefits for patients. 8 The LightCycler SeptiFast Test (SeptiFast, Roche Diagnostics) is a multipathogen probe-based real-time polymerase chain reaction (PCR) system targeting DNA sequences of bacteria and fungi in blood samples, and it is considered to be a potentially valuable complementary tool in the management of patients with suspected sepsis.…”
mentioning
confidence: 99%
“…Blood culture rarely isolates causative organisms after initiation of antibiotic therapy. 15,25 Antibiotics decrease the yield of blood cultures, and routine collection of blood samples may not be helpful in allo-SCT recipients. However, our study revealed a high incidence of 'occult' BSI in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a blood pathogen represents a negative prognostic factor, but the isolation of such pathogen is important for verifying the appropriateness of antibiotic therapy, which in turn is known to reduce morbidity and mortality (Grace, et al, 2001). Also, falsepositive results due to bacterial contaminants may lead to unnecessary antibiotic therapy, longer hospital stays and selection of resistant microorganisms (Bates, et al, 1991).…”
Section: Introductionmentioning
confidence: 99%